The Influence of Rest Period Instructions on the Default Mode Network - Benjamin, Christopher; Lieberman, Daniel A.; Chang, Maria; Ofen, Noa; Whitfield-Gabrieli, Susan; Gabrieli, John D.; Gaab, Nadine (Frontiers in Human Neuroscience, 2010)
The default mode network (DMN) refers to regional brain activity that is greater during rest periods than during attention-demanding tasks and many studies have reported DMN alterations in patient populations. It has also been shown that the DMN is suppressed by scanner background noise (SBN), which is the noise produced by functional magnetic resonance imaging (fMRI). However, it is unclear whether different approaches to “rest” in the noisy MR environment can alter the DMN and constitute a confound in studies investigating the DMN in particular patient populations (e.g., individuals with schizophrenia, Alzheimer’s disease). We examined twenty-seven healthy adult volunteers who completed an fMRI experiment with 3 different instructions for rest: (1) relax and be still, (2) attend to SBN, or (3) ignore SBN. Region of interest (ROI) analyses were performed to determine the influence of rest period instructions on core regions of the DMN and DMN regions previously reported to be altered in patients with or at risk for Alzheimer’s disease or schizophrenia. The dorsal medial prefrontal cortex (dmPFC) exhibited greater activity when specific resting instructions were given (i.e. attend to or ignore SBN) compared to when non-specific resting instructions were given. Condition-related differences in connectivity were also observed between regions of the dmPFC and inferior parietal/posterior superior temporal cortex. We conclude that rest period instructions and SBN levels should be carefully considered for fMRI studies on the DMN, especially studies on clinical populations and groups that may have different approaches to rest, such as first-time research participants and children.